Geochemistry and zircon U-Pb-Hf isotopes of the late Paleoproterozoic Jianping diorite-monzonite-syenite suite of the North China Craton: Implications for petrogenesis and geodynamic setting - Wang, Wei; Liu, Shuwen; Bai, Xiang; Li, Qiugen; Yang, Pengtao; Zhao, Yue; Zhang, Shuanhong; Guo, Rongrong (Lithos, 2013)
The late Paleoproterozoic Jianping diorite-monzonite-syenite suite (JDMSS), in the Western Liaoning Province (WLP) along the northern margin of the North China Craton (NCC), is composed mainly of magnetite diorites, clinopyroxene monzonites, syenites, and quartz syenites. LA-ICP-MS zircon U-Pb isotopic dating indicates that this complex emplaced between 1696 and 1721 Ma, almost synchronously with the 1680-1750 Ma anorthosite-mangerite-alkali granitoid-rapakivi granite suite (AMGRS) in northern Hebei Province. The JDMSS in the WLP is the eastwards extensional part of the AMGRS in northern Hebei Province along the northern margin of the NCC. All samples from the JDMSS are characterized by a wide and continuously variable geochemical spectrum of 463-64.9 wt.% SiO2 and 0.528-4.14 wt.% MgO, with high K2O (1.080-7.01 wt.%) and total alkalis (Na2O + K2O, 5.08-12.55 wt.%). These rocks are enriched in LREEs and LILEs but depleted in HFSEs (Nb, Ta, and Ti), and they show negative zircon epsilon(Hf)(t) values of -12.6 to -0.3 and a low whole-rock initial Sr-87/Sr-86 value of 0.703564. These geochemical features, together with trace element modeling, suggest that all the rocks of the JDMSS were generated chiefly by fractional crystallization of a common parental magma that was derived by partial melting of an amphibole-bearing enriched subcontinental lithospheric mantle source (mixed EMI and HIMU mantle), and that the magma assimilated crustal materials during ascent and emplacement. Integrating our data with those of previous studies of the contemporaneous magmatic rocks throughout the NCC (mafic dykes, volcanic rocks, and AMGRS; 1680-1780 Ma), we propose that both the northern and southern margins of the NCC, as well as the TNCO (Trans-North China Orogen), evolved under a post-collisional tectonic setting during the late Paleoproterozoic, postdating the final amalgamation of the NCC, and that the NCC at this time was probably located between Laurentia (North America and Greenland) and Siberia within the interior of the Columbia supercontinent. (C) 2013 Elsevier B.V. All rights reserved. Geochemistry & Geophysics Mineralogy SCI(E) 20 ARTICLE 175-194 162